The Role of Mass Communication in Shaping Changes in Culture and People's Behavior in Indonesia - Dedy Djamaludin Malik (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
This research is a type of qualitative research, using descriptive methods, while the purpose of this study is to determine the role of mass communication in shaping changes in culture and behavior of people in Indonesia, and the results of this study explain that, the development of communication technology in this modern century as an advancement in the field of culture that is mass, so that its influence also occurs in all aspects of human life, both urban communities and people who are far from government centers also experience changes that occur as a result of the development of communication technology. Technology and culture itself basically grows and develops along with the progress of human civilization which has been preceded by a concept of religion and the state, but when viewed in detail the rapid progress of the existing information technology system has had a very diverse impact on human growth and development as a whole, both on the positive side and vice versa. Seeing the effectiveness and role of the mass media is so great as one of the important components for the formation of people's personality, as well as the behavior and experience of public awareness. Therefore, many community groups are trying to make the mass media as a means of propaganda ideas, ideals, values and norms that they want to create. In addition, the mass media can also change the lifestyle or local culture by influencing the way of thinking of a particular group or community to like or follow something new or foreign to them.